Use of the patient-reported outcomes measurement information system (PROMIS®) to assess late-onset Pompe disease severity - Melodi Harfouche; Priya S. Kishnani; Eva Krusinska; Jamie Gault; Sheela Sitaraman; Amanda Sowinski; Irina Katz; Stephanie Austin; Margi Goldstein; Andrew E. Mulberg (SpringerOpen, 2020)
Abstract Background Patient-Reported Outcomes provide an opportunity for patients to establish dialogue with pharmaceutical or biotechnology companies about their health conditions without interpretation by a clinician or anyone else. However, Patient-Reported Outcomes that can be widely applicable for use in patient-focused drug development or clinical trial designs are not yet validated for all diseases. The aim of this study report was to provide supportive evidence of the construct and content validity of selected Patient-Reported Outcomes Measurement Information System (PROMIS®) questionnaires compared with other disease-relevant clinical outcome measures, including the 6-Minute Walk Distance, forced vital capacity, and Manual Muscle Test, in late-onset Pompe disease and to provide supportive evidence that the selected PROMIS measures are relevant and important to these patients. Methods Thirty patients with late-onset Pompe disease completed five PROMIS questionnaires that were chosen based on patient and provider feedback, along with discussion with key opinion leaders who are experts in Pompe disease. The Amicus Pompe Patient Advisory Board also provided patient experience feedback using the PROMIS questionnaires. Clinical outcome measures (6-Minute Walk Distance, forced vital capacity, and Manual Muscle Test) were collected at the Duke University Pompe Disease Clinical Research Program during a single visit. Results The Patient Advisory Board rated the questionnaires as representative of an unmet need. Correlation data demonstrated moderate to strong correlations of PROMIS questionnaires with the specified clinical outcome measures (6-Minute Walk Distance, forced vital capacity, and Manual Muscle Test). These data supported the construct and content validity of the PROMIS questionnaires because they confirmed the motor signs and symptoms of functional disability observed in patients with Pompe disease. Conclusions The correlations indicate that the clinical outcome measures assess important concepts related to patient-reported experiences. The Patient Advisory Board findings suggest that the selected PROMIS questionnaires are meaningful and address important concepts to patients with Pompe disease. The data were collected from a small number of patients at a single time point; further studies are needed with additional PROMIS questionnaires, which should include measures of motor function and health-related quality of life, in a larger number of patients followed up longitudinally.